Brexpiprazole for the treatment of schizophrenia. (1st February 2016) - Yee, Anne
ABSTRACT: Brexpiprazole (OPC-34712) is a novel serotonin-dopamine activity modulator, which has recently been approved by the U.S Food and Drug Administration for the treatment of schizophrenia. The aim of this paper is to systematically synthesize all data of the efficacy, safety and tolerability of Brexpiprazole in treating schizophrenia. The terms 'Brexpiprazole', 'OPC-34712' and 'schizophrenia' were searched. A total of 12 clinical trials with 7 available data records were found. The pooled effect size of Brexpiprazole 1 mg, 2 mg and 4 mg were all superior to placebo in terms of the change from baseline in positive and negative syndrome scale (PANSS) total score at week 6 (weighted mean difference = −3.74, p = 0.044; weighted mean difference = −5.76, p < 0.01 and weighted mean difference = −7.03, p < 0.01, respectively) when compared to that of the placebo in treating acute schizophrenia. Brexpiprazole displays a good safety and tolerability profile. The incidence of akathisia, headache, insomnia, sedation, agitation, diarrhea, weight gained, nausea, and dyspepsia are comparable to placebo.